THERMODYNAMIC STUDY OF NICKEL EXTRACTION PROCESS IN POMALAA, SULAWESI TENGGARA - TARUMINGKENG (NIM : 20214020), STEPHANIE
Nickel is one of mineral that is widely spread in Southeast Sulawesi region. Nickel processing into commercial metals so declared, because of government regulations about the increasing value-added of minerals through processing and purification of minerals. Nickel processing in Pomalaa, Southeast Sulawesi using pyrometallurgy process (extraction with high temperature) that performed in smelter where chemical process occur which involved thermodynamic variables. The purpose of this research is study the concept of thermodynamics to determine the thermodynamic variables that could control the processing of nickel in order to obtain the optimal results. Thermodynamic equilibrium of a chemical reaction (Gibbs potential) is used to see the processing of nickel occur spontaneously or not, and see the connection between thermodynamic variables in the processing of nickel. The results showed that the temperature and pressure were the thermodynamic variables that could control the processing of nickel, where those variables could be measured. Control needs to be done through measuring instruments, which was installed in the reactor (smelter) and connected to other equipments (mechanical) which then performs the changes according to necessary conditions to stabilize the process.